Anisotropic g factors of the tetragonal Cu2+ monomer in Tl-2223 superconductor - Zhang, Zhi-Hong; Wu, Shao-Yi; Kuang, Min-Quan; Ding, Chang-Chun (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
The gyromagnetic factors of the Cu2+ monomer in Tl-2223 superconductor are quantitatively investigatedfrom the perturbation formulas of these factors for a 3d9 ion in a tetragonally elongated octahedron. The local tetragonal distortion of the system is attributable to the axial elongation along c axis, corresponding to the five-fold coordinated Cu2+(2) site with almost 30% longer Cu–O bond length for the apical oxygen as compared to thefour planar ones. The significant anisotropic behaviors of the EPR spectra perpendicular to and parallel with the ab (CuO2) layers are analyzed on the basis of the local tetragonal elongation.